Setaman flower lexicons in the Nyekar rite: Anthropolinguistics of Javanese society - Salamah, Salamah; Nazilah, Halimah Milladunka; Agistina, Fanya Indah; Zakiyah, Millatuz (LITERA, 2024)
The tradition of carrying setaman flowers in the nyekar rite success to be a part of local wisdom that has survived through various periods, but on the other hand, documents about it are still limited.  This study aims to describe the lexicons in kembang setaman in the nyekar rite from the Javanese perspective. Adopting qualitative  method with a focus on ethnographic approach, data is collected through interview and literature study and examined using semiotic and lexical-semantic analysis. The result show seven plants that make up the setaman, including (1) roses (mawar or mawi-arsa, a sincere intention to live up to noble values), (2) jasmine (melati or melat ing ati, the sincerity of the heart), (3) white chrysolite flower (kanthil or tansah kumanthil-kanthil, uninterrupted devotion), (4) ylang (kenanga or kenangen ing angga, always remembering the ancestral heritage), (5) tuberose (sedap malam or harum dhalu, always remembering the sacred teachings of the ancestors even in the dark of the night), (6) rose balsam (pacar air or pacar banyu, prosperity continues to flow), and (7) pandan leaves (liaison with the deceased). Kembang setaman functions as a symbol of gifts accompanied by prayers sent when visiting graves which are considered homes for people who have died, and contemporary Javanese society is still carrying out this tradition. This research expands the limited field of Anthropolinguistics studies, and on the other hand, can be used as cultural documentation that encourages the intention to better conserve the local wisdom over a long period.